2015
DOI: 10.1088/0741-3335/58/1/014038
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic laser nano-plasmonics for effective fast particle production

Abstract: Particle acceleration and X-ray generation in different nano-structured targets irradiated by high intensity laser pulses of high contrast have been studied. It is found that maximal energy of fast particles and its directionality can be significantly enhanced, by choosing nano-structured targets. Generation and propagation of fast electrons in laser targets consisting of nano-wires are studied. Such targets exhibit a large conversion of laser energy into electron kinetic energy. An electron bunch can propagat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 26 publications
3
27
0
Order By: Relevance
“…As previous studies have not considered this separation it is difficult to make a straightforward comparison of the key results of this paper. However it can still be noted that, based on the total absorption also presented in Figure 5, our findings agree with previous studies of similar setups on, e.g., an optimal structure size of around d/λ = 1/2 and a total absorption of above 50% [42,43].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…As previous studies have not considered this separation it is difficult to make a straightforward comparison of the key results of this paper. However it can still be noted that, based on the total absorption also presented in Figure 5, our findings agree with previous studies of similar setups on, e.g., an optimal structure size of around d/λ = 1/2 and a total absorption of above 50% [42,43].…”
Section: Resultssupporting
confidence: 93%
“…Most notably, the energy source is the laser pulse, and there is of course a limit on how much energy one can transfer from the laser to the target (and, therefore, to the ions). Theoretical and experimental studies show that the energy absorption can be significantly increased by structures on the surface [32,[36][37][38][39][40][41], and the absorption can potentially be close to 100% [42,43]. As a natural continuation of these studies, we consider here how the structures affect the partitioning of the absorbed energy between the low and high energy electrons as well as between their normal and transverse motion.…”
Section: Introductionmentioning
confidence: 99%
“…Different approaches such as varying the target thickness [8], nanostructuring the back surface of the target [9,10] or growing a layer of low density foam [11][12][13] have already been studied. Several publications have reported that adding periodic nanostructures on the target front surface enhances drastically the laser energy absorption [13][14][15][16][17][18][19][20][21]. This generates ions with much higher energies than the ones obtained when targets with a flat surface are used [13,[20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Several publications have reported that adding periodic nanostructures on the target front surface enhances drastically the laser energy absorption [13][14][15][16][17][18][19][20][21]. This generates ions with much higher energies than the ones obtained when targets with a flat surface are used [13,[20][21][22][23][24][25][26][27][28][29][30]. The nature of this enhancement is still a matter of discussion, however it is known that it is strongly dependent on the shape of the structures, as well as on the angle of incidence of the impinging laser [13-15, 17, 18, 21, 22, 26, 27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation